Paths of internationalization of Polish enterprises - Beata Anna Glinkowska (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
The variability of the environment, saturation of the domestic market, the need to remain competitive, etc. require enterprises to search for new solutions in the fields of management and operation. Managers are confronted with new challenges. The internationalization of enterprises became an increasingly occurring pattern of cooperation and collaboration, resulting from the need to seek new markets and new opportunities, as well as the need to survive on the market. The article presents some chosen aspects of internationalization of enterprises, with a particular focus on the specifics of the internationalization of Polish companies of micro, small and medium size. The article presents the motives that guide entrepreneurs and managers, allowing them to expand their business activities to foreign markets. Also, it shows the barriers, which occur most frequently in the process of internationalization. The conducted empirical studies became the basis for presenting the ways of internationalization of Polish enterprises from the SME sector. The results were then referred to the conditions present in Poland and to the existing models. The article was written based on the analysis of literature and own research.